Environmentally Conscious Workforce: How Human Resource Management Drives Green Practices in Government - Rakhma, Nilam Adini; Pawestri, Rifka Resi; Maesaroh, Maesaroh; Widowati, Nina (Universitas 17 Agustus 1945 Surabaya, 2025)
Over the past few decades, human resource (HR) management in the public sector of the Indonesian state has undergone significant changes in response to internal and external pressures, which have compelled the Indonesian government to redefine its boundaries and enhance its public administration capabilities. As part of the current HR strategy, these reforms call for a more flexible, adaptive, and comprehensive HR system, including the implementation of Green Human Resource Management (GHRM). In several aspects of HR management, such as green recruitment, green training and development, and green rewards and compensation, GHRM integrates environmental sustainability practices. The primary objective of this study is to examine the role of human resource management in promoting green practices within the Indonesian government sector. The research approach uses a literature review analysis of the Scopus database. The results show that implementing GHRM in Indonesia's public sector still faces several challenges. However, with a comprehensive strategy, policy reform, and government commitment, GHRM has the potential to be a strategic solution in improving the effectiveness of public sector management, accelerating the achievement of the Sustainable Development Goals (SDGs), and supporting all government organizations in overcoming environmental and administrative challenges.